Assessment of 5-year system-wide type 2 diabetes control measures in a Southeast Asian metropolis - Wiroj Jiamjarasrangsi (2018)
Background: Sparse information exists regarding the progress of the chronic care model (CCM) implementation for type 2 diabetes, at system-wide level for developing countries including Thailand. Objective: We assessed the extent to which type 2 diabetes patients in Bangkok, Thailand report having received CCM-based services by using the Patient Assessment of Chronic Illness Care (PACIC). Methods: One thousand type 2 diabetes patients from 64 healthcare facilities throughout Bangkok were randomly selected, data about the extent they have received CCM-based services, their dietary, physical activity, medication-taking behaviors, body mass index (BMI), and blood sugar control status were collected by a set of structured questionnaires and medical record abstraction. Results: PACIC and self-management scores for patients receiving care from public hospitals and health centers were significantly higher than those from private hospitals. Being the primary care unit (PCU) - where the CCM implementation has been enforced since 2008 was significantly associated with higher PACIC scores for public hospitals. This was not the case for private hospitals. PCU status was significantly associated with better selfmanagement scores for patients in both public and private hospitals. However, variations in PACIC and selfmanagement scores did not reflect to BMI or glycemic control outcomes of the patients. Conclusion: There is encouraging evidence of progress of CCM implementation for type 2 diabetes patients in Bangkok, Thailand. This had also resulted in improved self-management, but not physiological or metabolic outcomes.